The Effectiveness Of Applying Arabic Teaching Materials in Al Arabiyah Baina Yadaik At Tanjung Pinang Senior Islamic High School - Amrul Luhfi (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the effectiveness of learning Arabic language skills using the Al-'Arabiyyah Bayna Yadaik textbook in improving Arabic language skills for teachers and students in MAN Tanjungpinang City Dormitory. This research is field-based (field research) because the data obtained from respondents and informants uses more techniques and methods of collecting field data. The respondents involved in this study were two Arabic language teachers and 20 students at the MAN Tanjungpinang dormitory who were randomly selected with predetermined criteria. As shown by the results of the tests conducted on the respondents, the results of the study indicate that the book Al-'Arabiyyah Bayna Yadaika is quite effective in an effort to improve the mastery of Arabic language proficiency of teachers and students in MAN Tanjungpinang City Dormitory.